FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITY PADA PERUSAHAAN YANG TERDAFTAR DI BEI - WIBOWO, SATRIYO; SUHENDRO, LEONY CHRISTINE (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
This study aims to assess the impact of firm size, growth, liquidity, and leverage on profitability. The sample consists of 15 companies in the food and beverage sector listed on the Indonesia Stock Exchange over a period of 7 years, from 2016 to 2022. Sampling was conducted using purposive sampling method, utilizing annual financial data of the companies as secondary data. Analysis was performed using EViews 12 software to obtain descriptive statistics and hypothesis testing, with multiple regression analysis as the chosen hypothesis testing method. The research findings indicate that firm size, growth, liquidity, and leverage have an impact on profitability. However, the tangibility variable does not affect profitability.